2013
DOI: 10.7554/elife.00348
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic conservation at gene regulatory elements revealed by non-methylated DNA profiling in seven vertebrates

Abstract: Two-thirds of gene promoters in mammals are associated with regions of non-methylated DNA, called CpG islands (CGIs), which counteract the repressive effects of DNA methylation on chromatin. In cold-blooded vertebrates, computational CGI predictions often reside away from gene promoters, suggesting a major divergence in gene promoter architecture across vertebrates. By experimentally identifying non-methylated DNA in the genomes of seven diverse vertebrates, we instead reveal that non-methylated islands (NMIs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
251
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(278 citation statements)
references
References 71 publications
27
251
0
Order By: Relevance
“…Additionally, we demonstrate that DNA methylation inhibits H3K27me3 deposition at CpG-rich sequences and that this inhibition can be reversed upon chemical removal of DNA methylation. These observations readily explain the occupancy of H3K27me3 and DNA methylation observed throughout the genome (23,24,33,34). They extend previous studies that already suggested a role for CpG dinucleotides in PRC2 recruitment (22,23) but are also more comprehensive and provide novel mechanistic details.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Additionally, we demonstrate that DNA methylation inhibits H3K27me3 deposition at CpG-rich sequences and that this inhibition can be reversed upon chemical removal of DNA methylation. These observations readily explain the occupancy of H3K27me3 and DNA methylation observed throughout the genome (23,24,33,34). They extend previous studies that already suggested a role for CpG dinucleotides in PRC2 recruitment (22,23) but are also more comprehensive and provide novel mechanistic details.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, loss of Polycomb recruitment coincides with increased susceptibility to DNA methylation. This finding is compatible with the observation of increased H3K27 methylation upon global loss of DNA methylation (23,24,33,34), which we also observe in our genome-wide datasets (Fig. S7A).…”
Section: Dna Methylation and H3k27me3 Recruitment Exclude Each Other Atsupporting
confidence: 92%
See 1 more Smart Citation
“…Our NanoString and in situ data raise the intriguing possibility that DNMT3B could regulate de novo methylation and subsequent repression of genes involved in the maintenance of neural crest progenitors and EMT, thus preventing continuous neural crest formation. CpG island promoters were recently shown to be largely hypomethylated, even when silenced on different tissues and developmental stages in many vertebrate models (19); thus, we examined the presence of CpG islands in the promoter 0DNMT3B). Treated embryos were characterized as having a strong or a mild prolonged emigration phenotype using the Sox10 marker.…”
Section: Loss Of Dnmt3b Results In Excess Migrating Neural Crest Andmentioning
confidence: 99%
“…promoters seems substantially lower in amphibians and fish [10]. However, this is likely due to the fact that the definition of the CpG island relies on arbitrary thresholds set upon C+G content, observed over expected ratio of CpG dinucleotide counts and region length [11], which have been optimised for mammalian genomes and do not perform well for genomes with very different nucleotide composition.…”
mentioning
confidence: 99%